12. Additional Effect Of Soybean Waste Probiotic And Palm Kernel Fermented With Aspergillus Niger (Akbis Prob) On The Growth Of Boiler Bone - Nurliana Nurliana; Aprilia Tanjung; Mustafa Sabri; Dian Masyitah; Muhammad Jalaluddin; Rastina Rastina (Jurnal Medika Veterinaria, 2019)
This study aimed to determine the bone growth of broiler chickens fed with additional probiotic Aspergillusniger (AKBIS Prob). The organ taken was the femur bone. A total of 24 broiler chickens reared with additional feed on 4 treatments and 3 repetitions with a combination of additional feed namely P0 (commercial feed), P1 (commercial feed and 2% AKBIS Prob), P2 (commercial feed and 4% AKBIS Prob) and P3 ( commercial feed and 6% AKBIS Prob). The sampling of the femur bone was carried out on chicken 21 and 35 days old and observed histologically after stained with hematoxylin-eosin (HE). The results showed from the examination of macroscopic growth that the femur growth increased more at the age of 35 days compared to the age of 21 days in the treatment group P1, P2 and P3 who were given probiotic Apergillusniger (AKBIS Prob) where the amount of Ca and P required for growth can be fulfilled. On microscopic examination, the measurement parameters were the number of active osteoblasts and osteoblast that looked more passive on the 35th day of treatment, compared to the age of 21 days. While the number of osteoclasts was more at age 21 than at age of 35 days in the treatment group who were given probiotic Aspergillusniger (AKBIS Prob)as additional food.